FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA ALIH FUNGSI LAHAN PERTANIAN DI KABUPATEN MINAHASA TENGGARA - Christianto ., Pondaag; Caroline B. D. Pakasi; Ribka M. Kumaat (AGRI-SOSIOEKONOMI, 2018)
The research was purposed to analysis factors that affecting to land conversion from agriculture to non agriculture at Southeast Minahasa Regency. Variables are in analysis is total population , PDRB capita and total industries. This research was done by used secondary data obtained from Central Statistics Agency of Southeast Minahasa Regency. Secondary data collected are Total population, PDRB per capita and total industries in Southeast Minahasa Regency by times series data. Data analysis is done using multiple linear analysis. The result research showed that only Population which affecting significantly to the decrease the land of agriculture area in Southeast Minahasa Regency. Increasing total population make a demand for the land of residence area continues to increase. That impact on the land of agriculture area was tends to decrease.*jnkd*